1998
DOI: 10.1021/ja974301t
|View full text |Cite
|
Sign up to set email alerts
|

Air Stability of Alkanethiol Self-Assembled Monolayers on Silver and Gold Surfaces

Abstract: Surface Raman spectroscopy, electrochemistry, and X-ray photoelectron spectroscopy have been used to study the effects of air exposure on the stability of self-assembled monolayers (SAMs) formed from alkanethiols on mechanically polished, smooth Ag and Au surfaces. Raman spectra exhibit oxidized sulfur modes after only hours of air exposure. X-ray photoelectron spectroscopy of the S 2p region provides additional evidence for sulfur oxidation. Cyclic voltammetry of Ru(NH3)6 3+ indicates that oxidized alkanethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
494
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 509 publications
(527 citation statements)
references
References 37 publications
32
494
1
Order By: Relevance
“…In addition, we have confirmed that the modes associated with the sulfur oxidation analyzed in Ref. 31 were not observed in our measurements either. …”
Section: Resultssupporting
confidence: 90%
“…In addition, we have confirmed that the modes associated with the sulfur oxidation analyzed in Ref. 31 were not observed in our measurements either. …”
Section: Resultssupporting
confidence: 90%
“…51 We note that experiments by Schoenfisch and Pemberton suggest ozone as the primary oxidant in ambient laboratory air. 52 The oxidized SAM is far less strongly bound to the gold, 53 and hence drastically compromises the viability of the final molecular device. The stability over time is particularly an issue when long multi-step fabrication processes are employed, such that the alkanethiol layer has time to oxidize, and with assemblies on nanoparticles, where the high radius of curvature makes it easy for oxygen to reach the gold-thiolate bond.…”
Section: Alkanethiol and Organosulfur Self-assembled Monolayermentioning
confidence: 99%
“…Studies suggest that these monolayer-protected clusters are stable in air at room temperature for 6 months. Recently, we have shown that ozone can oxidize the monolayer [71], as in the case of 2D SAMs [72]. Sulfur head-group gets oxidized, and this results in desorption of some of the molecules as evidenced by the loss of intensity of the CH modes in the IR spectrum.…”
Section: © 2002 Iupac Pure and Applied Chemistry 74 1593-1607mentioning
confidence: 99%